(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2016)
Epilepsy is a brain disorder characterized by partial or generalized spontaneous (unprovoked) recurrent epileptic seizures and often, comorbidities such as anxiety and depression. Epilepsy is fourth most common neurological disorder. In developed countries, new cases occur of epilepsy in babies and elderly due to the differences in the frequency of disease causes. All available antiepileptic drugs have antiepileptogenic effects; they only prevent the development or progression of epilepsy. However, no drugs have been reported with epileptogenesis effect. This computational research investigation provides the pharmacokinetic, bioactivity and toxicity profiles of some selected antiepileptic agents that would be useful for development of new antiepileptic molecule having good pharmacological profile.